Clinical and Epidemiological Factors Associated with Mortality in Parkinson’s Disease in a Brazilian Cohort - Gustavo Costa Fernandes; Mariana Peixoto Socal; Artur Francisco Schumacher Schuh; Carlos R. M. Rieder (Parkinson's Disease)
Background. Prognosis of PD is variable. Most studies show higher mortality rates in PD patients compared to the general population. Clinical and epidemiologic factors predicting mortality are poorly understood. Methods. Clinical and epidemiologic features including patient history and physical, functional, and cognitive scores were collected from a hospital-based cohort of PD patients using standardized protocols and clinical scales. Data on comorbidities and mortality were collected on follow-up. Results. During a mean follow-up of 4.71 years (range 1–10), 43 (20.9%) of the 206 patients died. Those who died had higher mean age at disease onset than those still alive at the last follow-up (67.7 years versus 56.3 years; p<0.01). In the univariate analysis, age at baseline was associated with decreased survival. In the adjusted Cox proportional hazards model, age at disease onset and race/ethnicity were predictors of mortality. Conclusions. Late age at disease onset and advanced chronological age are associated with decreased survival. Comorbidities and PD characteristics were not associated with decreased survival in our sample. Race/ethnicity was found in our study to be associated with increased hazard of mortality. Our findings indicate the importance of studying survival among different populations of PD patients.